Effect of fiber type on the behavior of cementitious composite beam-column joints under reversed cyclic loading. (20th October 2018) - Ismail, Mohamed K.; Abdelaleem, Basem H.; Hassan, Assem A.A.
Highlights: ECC beam-column joints under reversed cyclic loading were investigated. Different types of polymeric and steel fibers were tested. Hysteresis behavior, ductility, energy dissipation, and cracking were evaluated. ECC beam-column joints showed improved ductility compared to NC joint. Joints with steel fibers showed the best behavior under cyclic loading. Abstract: This paper investigates the effect of using different types of fiber on the behavior of engineered cementitious composite (ECC) beam-column joints under reversed cyclic loading. The tested ECC beam-column joints were cast with different types of fiber, including 8 mm and 12 mm polyvinyl alcohol fibers (PVA8 and PVA12), 13 mm polypropylene fibers (PP13), and 13 mm steel fibers (SF13). The investigation also tested a conventional normal concrete (NC) beam-column joint made with 10 mm coarse aggregate for comparison. The performance of the tested specimens was evaluated based on hysteresis behavior, ductility, energy dissipation capacity, and cracking behavior. The results indicated that compared to NC, ECC with either PVA or PP fibers can be a promising construction material to develop beam-column joints with improved ductile behavior under reversed cyclic loading. Using shorter PVA fibers (PVA8 vs. PVA12) appeared to have a stronger influence on improving the cyclic behavior of ECC joints. The highest improvements in terms of first crack load, ultimate load, ductility, and energy dissipation capacity were observed when SF13 was used. The results also indicated that the failure pattern of all ECC joints showed better cracking behavior and higher shear strength compared to the NC joint.